Isolation and structural elucidation of a novel homogenous polysaccharide from Tricholoma matsutake. Issue 1 (2nd January 2016) - Cheng, Hua; Jia, Yan; Wang, Ling; Liu, Xiaoying; Liu, Guangrong; Li, Li; He, Congfen
Abstract : A crude polysaccharide possessing antitumour, radiation-resistant and anti-ageing attributes was extracted from Tricholoma matsutake by water extraction and alcohol precipitation. From this crude polysaccharide, a homogeneous polysaccharide, TMP-5II, was successfully purified by Sephacryl S-300 column chromatography. The average molecular weight ( M w ) of TMP-5II was 15.76 kDa. Monosaccharide analysis indicated that the homogeneous polysaccharide contained four different residues:d -glucose, d -galactose, d -mannose andd -fucose. Attenuated total reflectance infrared spectroscopy revealed characteristics typical of carbohydrate polymers and a peak typical of a β-type glycosidic bond. TMP-5II was selected for structural characterisation by nuclear magnetic resonance (NMR) analysis. According to 1 H NMR, 13 C NMR and two-dimensional-NMR analysis, TMP-5II contains two kinds of linkages, β and α, at a ratio of 4:1. Preliminary results indicated that the polysaccharide had (1-4)-beta-pyran glucose as the main chain, and a branched chain in the O-6 location with fucose (1-2) mannose (1-3)-alpha-pyran galactose. Abstract :